Population pharmacokinetic analysis of ulotaront in subjects with schizophrenia - Galluppi, Gerald R.; Polhamus, Daniel G.; Fisher, Jeannine M.; Hopkins, Seth C.; Koblan, Kenneth S. (CPT: pharmacometrics and systems pharmacology, 2021)
Ulotaront (SEP‐363856) is a trace amine–associated receptor 1 agonist with 5‐HT1A agonist activity in phase III development for the treatment of schizophrenia. The efficacy of ulotaront is not mediated by blockade of D2 or 5‐HT2A receptors. The aim of this study was to evaluate the population pharmacokinetics (PopPKs) of ulotaront in adult subjects using pooled data from seven phase I studies, one phase II acute study, and one 6‐month extension study. Single and multiple (up to 7 days) oral doses (5–150 mg/day) were studied in both healthy adult subjects (with intensive serial plasma sampling) and adult patients with schizophrenia (some with intensive and some with sparse plasma sampling). Ulotaront was well‐absorbed and exhibited dose‐proportionality in doses ranging from 10 to 100 mg, in mean maximum concentration, area under the concentration‐time curve, and minimum concentration. Moderate interindividual variability was observed in concentration‐time profiles. The estimated median time to maximal concentration was 2.8 h and the median effective half‐life was 7 h, corresponding to an exposure accumulation ratio of 1.10 at steady‐state with daily dosing. There was no indication of time‐dependent changes in PKs after up to 12 weeks of daily dose administration. No clinically meaningful effects on ulotaront PK parameters were observed based on race, age, sex, formulation (capsule or tablet), or clinical status (healthy volunteer vs. patient with schizophrenia); body weight was the only meaningful covariate.